An implementation study of the crisis resolution team model in Norway: Are the crisis resolution teams fulfilling their role? - Johnson Sonia; Ruud Torleif; Gråwe Rolf W; Hasselberg Nina (BMC, 2011)
Abstract Background The establishment of crisis resolution teams (CRTs) is part of the national mental health policy in several Western countries. The purpose of the present study is to describe characteristics of CRTs and their patients, explore the differences between CRTs, and examine whether the CRTs in Norway are organized according to the international CRT model. Methods The study was a naturalistic study of eight CRTs and 680 patients referred to these teams in Norway. Mental health problems were assessed using the Health of the Nation Outcome Scales (HoNOS), Global Assessment of Functioning Scales (GAF) and the International Statistical Classification of Diseases and Related Health Problems, 10th Revision (ICD-10). Results None of the CRTs operated 24 hours a day, seven days a week (24/7 availability) or had gate-keeping functions for acute wards. The CRTs also treated patients who were not considered for hospital admission. Forty per cent of patients waited more than 24 hours for treatment. Fourteen per cent had psychotic symptoms, and 69% had affective symptoms. There were significant variations between teams in patients' total severity of symptoms and social problems, but no variations between teams with respect to patients' aggressive behaviour, non-accidental self-injury, substance abuse or psychotic symptoms. There was a tendency for teams operating extended hours to treat patients with more severe mental illnesses. Conclusions The CRT model has been implemented in Norway without a rapid response, gate-keeping function and 24/7 availability. These findings indicate that the CRTs do not completely fulfil their intended role in the mental health system.